Oblique Intrathecal Injection in Lumbar Spine Surgery: A Technical Note. (8th May 2017) - Jewett, Gordon A.E.; Yavin, Daniel; Dhaliwal, Perry; Whittaker, Tara; Krupa, JoyAnne; Du Plessis, Stephan
Abstract: Objectives: Intrathecal morphine (ITM) is an efficacious method of providing postoperative analgesia and reducing pain associated complications. Despite adoption in many surgical fields, ITM has yet to become a standard of care in lumbar spine surgery. Spine surgeons' reticence to make use of the technique may in part be attributed to concerns of precipitating a cerebrospinal fluid (CSF) leak. Methods: Herein we describe a method for oblique intrathecal injection during lumbar spine surgery to minimize risk of CSF leak. The dural sac is penetrated obliquely at a 30° angle to offset dural and arachnoid puncture sites. Oblique injection in instances of limited dural exposure is made possible by introducing a 60° bend to a standard 30-gauge needle. Results: The technique was applied for injection of ITM or placebo in 104 cases of lumbar surgery in the setting of a randomized controlled trial. Injection was not performed in two cases (2/104, 1.9%) following preinjection dural tear. In the remaining 102 cases no instances of postoperative CSF leakage attributable to oblique intrathecal injection occurred. Three cases (3/102, 2.9%) of transient CSF leakage were observed immediately following intrathecal injection with no associated sequelae or requirement for postsurgical intervention. In two cases, the observed leak was repaired by sealing with fibrin glue, whereas in a single case the leak was self-limited requiring no intervention. Conclusions: Oblique dural puncture was not associated with increased incidence of postoperative CSF leakage. This safe and reliable method of delivery of ITM should therefore be routinely considered in lumbar spine surgery. RÉSUMÉ: Note technique à propos de l'injection intrathécale oblique lors d'une chirurgie à la colonne lombaire. Objectifs : L'injection intrathécale de morphine (ITM) est un moyen efficace d'analgésie postopératoire et aide à diminuer la douleur associée aux complications. Malgré son adoption dans plusieurs domaines chirurgicaux, l'ITM n'est pas encore devenue la norme en chirurgie de la colonne lombaire. La réticence des chirurgiens qui pratiquent ce type de chirurgie à utiliser cette technique pourrait être due en partie à la crainte de provoquer une fuite de liquide céphalorachidien (LCR). Méthodologie : Nous décrions une méthode d'injection intrathécale oblique pendant la chirurgie de la colonne lombaire pour minimiser le risque de fuite du LCR. Le sac dural est pénétré obliquement à un angle de 30° afin de décaler les sites de ponction au niveau dural et arachnoïdien. Une injection oblique dans le cas d'un accès dural limité est rendue possible en courbant une aiguille de calibre 30 à 60°. Résultats : La technique a été utilisée pour ITM ou injection de placebo chez 104 patients lors d'une chirurgie à la colonne lombaire dans le contexte d'une étude randomisée contrôlée. L'injection n'a pas été effectuée chez 2 sujets (2/104, 1, 9%) à cause d'une déchirure durale survenue préalablement. Chez les 102 autres sujets, aucune fuite de LCR attribuable à l'injection intrathécale oblique n'est survenue. Une fuite transitoire de LCR a été observée immédiatement après l'injection intrathécale chez 3 sujets (3/102, 2, 9%), sans séquelle associée ou nécessité de réintervention après la chirurgie. Chez 2 sujets, la fuite observée a été réparée en la scellant avec de la colle de fibrine alors que chez l'autre sujet aucune intervention n'a été nécessaire. Conclusions : Une ponction durale oblique n'a pas été associée à une incidence accrue de fuite du LCR en période postopératoire. Cette méthode sûre et fiable d'ITM devrait donc être envisagée de routine dans la chirurgie de la colonne lombaire.